The impact of strategic alignment and responsiveness to market on manufacturing firm's performance - Sardana, D.; Terziovski, Mile; Gupta, N. (Elsevier, 2016)
Drawing on dynamic capabilities theory and a sample based on the Indian manufacturing industry, we examine the influence of manufacturing operations' functioning, strategic alignment and responsiveness to market need for customization and firm performance. A multi-variate regression method is applied on the factors identified using confirmatory factor analysis. Our findings indicate that operations' strategic alignment to the firm's objectives is the single most key contributor to firm performance. The operations' capability to respond to market need for customization also significantly contributes to firm performance. Plant technology capability is also essential to respond effectively to market need for customization, and is positively and significantly related to firm performance. On the other hand, while delivery capability and cost control of the manufacturing operation are positively related to firm performance, they are not significant. Operations and marketing managers and firms' policy makers should emphasize operations' strategic alignment to firms' performance objectives, and build dynamic operational capability to be responsive to changing market needs.